PENGARUH CYBERBULLYING TERHADAP HARGA DIRI PADA DEWASA AWAL KORBAN CYBERBULLYING DI TWITTER - Pribadi, Rafli (Universitas Negeri Padang, 2023)
Cyberbullying is a behavior of a person or a group who repeatedly within a certain period of time intentionally spoken, insulted and threatens others which is carried out indirectly through the use of the internet, computers, cellphones, or other digital devices, in the case of this research is conducted through Twitter. This study aims to empirically examine the effect of cyberbullying on self-esteem in early adulthood victims of cyberbullying on Twitter. The research sample is consisted of 145 respondents obtained through purposive sampling technique. The results of this research hypothesis testing using a simple regression technique and obtained the regression value with significance of 0.000 (p <0.05). This indicates that cyberbullying has a very significant effect on self-esteem. It was also found in this study that cyberbullying affects self-esteem by 22.7% and the other 77.3% is influenced by external factors. Keywords: Cyberbullying, Self-Esteem, Early Adulthood, Victim, Twitter